Hubungan Kepemimpinan Transformasional dengan Kinerja Karyawan di Rumah Sakit Pangayoman Cipinang Jakarta Timur - rita, Yurita; Panjaitan, Ribka Sabarina; Ludovikus, Ludovikus; Octavia, Tesya; Saragih, Dameria; Setyaningsih, Tri; Ernawati, Ernawati; Dachliana, Dachliana; Imelda, Imelda; Feronica, Cindy; Oxana, Stefanova Oryza; Zahra, Faiza Al; Tobari, Mochamad Ichrom (Jurnal Dunia Kesmas, 2024)
Transformative leadership is one of the effective leadership styles in improving employee performance. Pengayoman Hospital Cipinang East Jakarta as one of the private hospitals in East Jakarta, needs effective leadership to improve the performance of its employees. This study aims to analyze the relationship between transformative leadership and employee performance at Pengayoman Cipinang Hospital, East Jakarta. Methods: This study uses a survey method using a questionnaire as a data collection instrument. The research sample consisted of 40 respondents from Cipinang Pengayoman Hospital, East Jakarta, which were randomly selected. The results of the study show that this correlation shows a strong positive relationship between the two variables with a significance value (Sig. 2-tailed) of 0.000, where an increase in Transformational Leadership tends to be followed by an increase in Performance. Conclusion: This study concludes that transformative leadership has a positive and significant relationship with employee performance at Pengayoman Hospital Cipinang East Jakarta. Therefore, it is recommended that the leadership of the East Jakarta Cipinang Nursing Hospital improve its transformative leadership skills to improve the performance of its employees. Keywords : Transformational Leadership, Performance, Employees, Hospital.